The Effect of Accelerated Learning (Shallow – Deep) in Attention Control and Learning Dribbling in Soccer - Abdulhur, Dhafer; Shihab, Ghada Moayad (Journal of Physical Education, 2022)
The research aimed at identifying the effect of accelerated learning (shallow – deep) on attention control and dribbling in soccer for first year college students as well as identifying differences among the four groups. The researchers used the experimental method on (56) freshmen from the college of physical education and sport sciences/ university of Baghdad. The subjects were divided into two experimental and two controlling groups who followed the accelerated program vs traditional program. The data was collected and treated using proper statistical operations to conclude that deep accelerated learning surpassed shallow accelerated learning group.